Kreatif dan dinamis dengan batu alam / Irwan Wijaya, Solehuddin ; editor Dewanti Nurcahyani, Lutfi Kurniawan. - IRWAN WIJAYA; Solehuddin; Dewanti Nurcahyani; Lutfi Kurniawan (Griya Kreasi, 2014)
139 hlm. ilus. ; 22 cm [3 eks.]